Diary of a wimpy kid: DOG DAYS - Kinney, Jeff (Amulet Books, an imprint of Abrams New York, 2018)
Collects the diaries of middle-schooler Greg Heffley as he faces the challenges of school, deals with his annoying older brother, misses the comforts of modern life when his town voluntarily goes electronics-free, and faces other challenges